2014
DOI: 10.1021/am502131t
|View full text |Cite
|
Sign up to set email alerts
|

Modified Two-Step Deposition Method for High-Efficiency TiO2/CH3NH3PbI3 Heterojunction Solar Cells

Abstract: Hybrid organic-inorganic perovskites (e.g., CH3NH3PbI3) are promising light absorbers for the third-generation photovoltaics. Herein we demonstrate a modified two-step deposition method to fabricate a uniform CH3NH3PbI3 capping layer with high-coverage and thickness of 300 nm on top of the mesoporous TiO2. The CH3NH3PbI3 layer shows high light-harvesting efficiency and long carrier lifetime over 50 ns. On the basis of the as-prepared film, TiO2/CH3NH3PbI3 heterojunction solar cells achieve a power conversion e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(152 citation statements)
references
References 30 publications
8
142
1
Order By: Relevance
“…The first perovskite solar cells with a PCE of 15 % [95] was achieved using this method compared with 9 % [27] that was reported using one-step spin-coating method. PCE of over 10 % [89,91] in hole conductor free perovskite solar cells has been achieved using this method compared with an initial value of 7.3 % [47]. It has been demonstrated that this method is more suitable for mesoporous-structured solar cells where the mesoporous layer formed by nanoporous network of TiO 2 can effectively confine PbI 2 nanocrystals to small sizes, where fully conversion of PbI 2 to MAPbI 3 perovskite only takes few minutes.…”
Section: Sequential Deposition Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…The first perovskite solar cells with a PCE of 15 % [95] was achieved using this method compared with 9 % [27] that was reported using one-step spin-coating method. PCE of over 10 % [89,91] in hole conductor free perovskite solar cells has been achieved using this method compared with an initial value of 7.3 % [47]. It has been demonstrated that this method is more suitable for mesoporous-structured solar cells where the mesoporous layer formed by nanoporous network of TiO 2 can effectively confine PbI 2 nanocrystals to small sizes, where fully conversion of PbI 2 to MAPbI 3 perovskite only takes few minutes.…”
Section: Sequential Deposition Methodsmentioning
confidence: 96%
“…Also, organic [71][72][73][74] or inorganic hole transporters [75,76] have been widely studied in organic solar cells [77][78][79], solid-state DSCs [80][81][82][83] and extremely thin absorber solar cells [84][85][86][87]. Interestingly, it has been recently reported that the ambipolar semiconducting nature of perovskite enabled the configuration of comparative solid-stated solar cells without any electron transport layer [88] or hole transport layer [48,[89][90][91][92]. Therefore, here we will mainly discuss progresses made to the perovskite layer in terms of the newly emerged perovskite solid-state solar cells.…”
Section: Components Of Perovskite Solid-state Solar Cellsmentioning
confidence: 99%
“…Between a hole transporting material (HTM) and an electron transporting material (ETM) perovskite layer is sandwiched together with metal electrode substrates of indium tin oxide (ITO)/fluorine tin oxide (FTO). Structure of employing mesoporous metal oxide materials (TiO 2 ) and planar heterojunction structure without mesoporous materials [18][19] are two major architecture of perovskite solar cells devices .…”
Section: Structure and Working Principlementioning
confidence: 99%
“…Li et al [7] reported an HTL-free device demonstrating unobvious J-V hysteresis with a remarkable efficiency of 16%. However, it still remains hard to facilely fabricate highly efficient devices and the demonstrated efficiency is mostly among 10%-12% [8][9][10]. And the reason why the HTL can be eliminated is not understood completely.…”
Section: Introductionmentioning
confidence: 99%